Improving the phase transition characteristic and latent heat storage efficiency by forming polymer-based shape-stabilized PCM for active latent storage system. (March 2022) - Rahmalina, Dwi; Rahman, Reza Abdu; Ismail
Abstract: In this work, form-stabilized PCM (SSPCM) is evaluated for an active latent heat storage (ALHS) system. High-density polyethylene (HDPE) and styrene-butadiene-styrene (SBS) are used as supporting materials. Four different composites are prepared based on weight ratio: pure paraffin (P), paraffin/HDPE (80/20), paraffin/SBS (80/20), and paraffin/HDPE/SBS (80/20 + 20). The variation in the thermal conductivity depends on the supporting material where HDPE is good at solid-phase and SBS in liquid-phase. According to the DSC results, the supercooling degree is decreased for the all-composite SSPCM with the lowest supercooling degree by 0.6 °C for paraffin/SBS. The thermogravimetric results for composite SSPCM show a higher temperature decomposition with multi-step degradation. The thermal performance of the sample is assessed by using a tube-in-shell heat exchanger. The isothermal phase transition is observed for all composite SSPCM with the lowest temperature gradient by 5 °C. The composite SSPCM has a higher storage efficiency ranging from 85.6 to 88.4% than pure paraffin, with a storage efficiency of 72.3%. With a stable phase transition and a better storage efficiency, the proposed SSPCM can improve paraffin-based ALHS.